Examining the Relationship Between Leaders' Power Use, Followers' Motivational Outlooks, and Followers' Work Intentions - Peyton, Taylor; Zigarmi, Drea; Fowler, Susan N. (Frontiers in Psychology, 2019)
From the foundation of self-determination theory and existing literature on forms of power, we empirically explored relationships between followers’ perceptions of their leader’s use of various forms of power, followers’ self-reported motivational outlooks, and followers’ favorable work intentions. Using survey data collected from two studies of working professionals, we apply path analysis and hierarchical multiple regression to analyze variance among constructs of interest. We found that followers’ perceptions of hard power use by their leaders (i.e., reward, coercive, and legitimate power) was often related to higher levels of sub-optimal motivation in followers (i.e., amotivation, external regulation, and introjected regulation). However, followers who perceived their leaders used soft power (i.e., expert, referent, and informational power) often experienced higher levels of optimal motivation (i.e., identified regulation and intrinsic motivation), but further investigation of soft power use is warranted. The quality of followers’ motivational outlooks was also related to intentions to perform favorably for their organizations.